Review of David Monod. 2005. Settling Scores: German Music, Denazification, and the Americans, 1945-1953. Chapel Hill: University of North Carolina Press - Tompkins, David (Current Musicology, 2006)
David Monod’s engaging and thorough monograph offers a largely convincing if at times overstated rebuttal to such negative assessments of the American role in the musical realm of postwar Germany. Through his focus on cIassical music, he argues that American influence helped to lay the foundations for a new and democratic cultural life. Perhaps most controversially, Monod claims that the modest cultural regeneration of the early postwar years was possible because of the “revolutionary and transformative” power of denazification, the policy to remove Nazi influences from public life (9). While he agrees with most scholars that denazification was implemented poorly and ended too quickly, he nonetheless maintains that American influence was positive in limited but essential ways, through the actions of individual cultural officers as well as in the structural reform of arts administration. Although many individual initiatives failed, he maintains that the denazification policies-both those designed to remove Nazis from public life as well as those intended to punish and rehabilitate individual Nazis and sympathizers-indeed implemented core democratic values and that, as a result, German musical life changed for the better.